Nilai-Nilai Pendidikan Agama Islam Dalam Film Dokumenter Covid-21 Karya Daniel Hernandez Torrado - Gita Syahara; Hasan Basri; Moh.Ahyan Yusuf Sya’bani (Jurnal Mahasiswa Pendidikan, 2022)
Values, Islamic Religion, Islamic Religious Education, Covid, Film Analysis. The message in the film, of course, there are positive and negative. Many people can easily catch the message from the film they watch, but many also find it difficult because they think that films are just entertainment. Many criticize someone who is analyzing a film, because for them it is a waste of time. It's actually not wrong, because everyone has the right to determine his own way how he will process the film. This type of research is descriptive qualitative. The subjects of this thesis research are: Film. This qualitative research method uses data collection techniques, namely: Observation and Documentation. The results of the study show that we can take some important messages contained in this film, so that we can understand that someone making a work like a film has a purpose that we need to understand.